The impact of social factors on outcomes in patients with bleeding disorders. (24th July 2015) - Holstein, K.; von Mackensen, S.; Bokemeyer, C.; Langer, F.
Abstract : Introduction: In haemophilia, clinical outcomes are mainly determined by the severity of clotting factor deficiency, treatment regimen, availability of clotting factor concentrate and age. Information about the relevance of patient‐related factors such as education, social status or impact of the disease on the patient's life is scarce. Aim: To assess the impact of social status and disease‐related impairment of certain aspects of the patient's life on clinical and psychosocial outcomes in patients with inherited bleeding disorders (PWBD). Methods: Consecutive patients of a single centre were assessed by questionnaires on social status and quality of life (SF‐36). Social status was defined by school and professional education, employment and financial income of patients as well as school education of their parents. Results: Fifty‐seven PWBD (mean age, 38 ± 16 years) were enrolled, 60% were treated on‐demand; PWBD had a median number of 2.5 (0–34) annual bleeds and a median orthopaedic joint score of 6 (0–38). No significant differences were found for clinical and psychosocial outcomes across social status groups. More than half of the patients reported that haemophilia had an impact on their school education, childhood and leisure activities. Patients with a high impact of haemophilia on their lives were less satisfied with their lives ( P  < 0.002), reported worse quality of life in all domains of the SF‐36, had a worse joint score ( P  < 0.024) and reported more pain ( P  < 0.013). Conclusion: The perceived impact of haemophilia on patients' lives seems to have a stronger impact on clinical and psychosocial outcomes than patients' actual social status.